Subacute tributyltin exposure alters the development and morphology of mammary glands in association with CYP19A1 expression in female rats - Silva, Natalia P.; da Costa, Charles S.; Barbosa, Kayke L.; Januario, Cidália de F.; Gama-de-Souza, Leticia N.; Breves, Cinthia; Fortunato, Rodrigo S.; Miranda-Alves, Leandro; de Oliveira, Miriane [UNESP]; Nogueira, Celia R. [UNESP]; Graceli, Jones B. (Elsevier, 2024)
Tributyltin (TBT) is an endocrine-disrupting chemical (EDC) related to reproductive dysfunctions. However, few studies have investigated the effects of TBT exposure on mammary gland development. Thus, we assessed whether subacute TBT exposure causes irregularities in mammary gland development. We administered TBT (100 and 1,000 ng/kg/day for 30 days) to female rats from postnatal day (PND) 25 to PND 55, and mammary gland development, morphology, inflammation, collagen deposition, and protein expression were evaluated. Abnormal mammary gland development was observed in both TBT groups. Specifically, TBT exposure reduced the number of terminal end buds (TEBs), type 1 (AB1) alveolar buds, and type 2 (AB2) alveolar buds. An increase in the lobule and differentiation (DF) 2 score was found in the mammary glands of TBT rats. TBT exposure increased mammary gland blood vessels, mast cell numbers, and collagen deposition. Additionally, both TBT rats exhibited intraductal hyperplasia and TEB-like structures. An increase in estrogen receptor alpha (ERα), progesterone receptor (PR), and cytochrome P450 family 19 subfamily A member 1 (CYP19A1) - positive cells was observed in the mammary glands of TBT rats. A strong negative correlation was observed between CYP19A1- positive cells and TEB number. In addition, CYP19A1 - positive cells were positively correlated with mammary gland TEB-like structure, ductal hyperplasia, inflammation, and collagen deposition. Thus, these data suggest that TBT exposure impairs mammary gland development through the modulation of CYP19A1 signaling pathways in female rats.
Keywords: CYP19A1; Mammary gland development; Toxicity; Tributyltin